Lessons from a Pluralist Approach to a Wicked Policy Issue - Jake Chapman (Integral Review, 2010)
The most difficult policy issues are those where there are profound disagreements about what is wrong, what should be done, and how things work. This paper describes a pluralist approach, based on the soft systems methodology, to youth nuisance on deprived estates in Manchester, UK, where there were profound disagreements between the agencies involved. When there are disagreements about the nature of the problem, its causes, or about how the system of interest actually functioned, a pluralist approach is required, and this is provided by Checkland’s soft systems approach. When the disagreements involve conflicts of value, it is necessary to adopt an adaptive approach that fosters change in the values, beliefs or behaviour of those involved. In the spectrum of public sector agencies involved, five different perspectives of agencies were identified, their descriptions indicating the need for the pluralist approach taken. The project was an experiment in using systemic approaches in public policy and the paper describes the learning associated with impacting outcomes. Processes used in the project included a “soft systems” workshop, which is described along with some effects on both the project participants and overall outcomes. The overall aim is to share the experience of this project so that it may inform those working with systemic approaches and other pluralist methods on wicked problems in the public sector.